Effect of Problem Complexity on Group Learning and Problem Solving Skills of Medical Students - Samia Sarwar, Shaista Ali, Nadeem Ikram, Abdullah Bin Khurram,Assad Kamal Sheikh, Muhammad Abdullah (Journal of Rawalpindi Medical College, 2016)
Background: To analyze the effect of problem difficulty on group learning and problem solving skills of second year MBBS students. Methods: In this prospective descriptive study two problem based learning (PBL) scenarios (one easy and the other difficult) were constructed on topic of hyperthyroidism were given consecutively to of 270 students (199 girls and 71 boys). At the end of two PBL scenarios, the students’ perceptions regarding group learning were recorded for both PBLs (easy and difficult) simultaneously using 5 point Likert scale on a standardized questionnaire. At the end of the difficult scenario, knowledge retention and problem solving skills of students were also tested by giving them a written test comprising of MCQs and SEQs. Data was analyzed by SPSS version 20 for frequencies and percentages. Paired Likert data regarding group learning items was analyzed using the Wilcoxon Signed Ranks test. Central tendency for positive and negative item outcomes were assessed to evaluate whether there is a significant directional change in the two responses. p value <0.05 was considered significant. Results: Wilcoxon Signed Ranks test indicated that the two testing conditions were not significantly different (z score, p>0.05). There was not a statistically significant difference between the simple and difficult scenario of PBL. Mean scores of the students were obtained as 0.92, 0.76, , 0.73, 0.53, 0.47 while for C-1 (recall) level MCQs mean scores are 0.79, , 0.61, 0.48 and0.19. For SEQs best mean score was again observed for one SEQ of C-2 level and it is found 0.79 while for C-3 level (Problem solving level) the mean score were 0.43 only. After accomplishing difficult PBL, students have shown better performance in C-2 level (interpretation level) questions as compared to C-1 (recall) and C-3 level (problem solving). Conclusion: There was significant difference in group work between during the simple and difficult PBL scenario. MCQs and SEQs of C-2 level (level of interpretation) were attempted well than C-1 and C3 level